The Effect of Nutrition Education Given to Healthcare Personnel on Orthorexia Nervosa - Dalğa, Derya; Öngün Yılmaz, Hande (Progress in Nutrition, 2021)
Objective: This study was conducted to determine the effect of nutritional education given to healthcare professionals on Orthorexia Nervosa. Methods: Within the scope of the study, 111 volunteer health personnel working in a private health institution received nutrition education. Before the education, the questionnaire form and ORTO-15 scale were applied to the participants by face-to-face interview technique, and their anthropometric measurements were taken by the researcher. ORTO-15 scale was applied again after the education. Results: Of the individuals who participated in the study, 75.7% were female, 24.3% were male and the mean age was 32.75±10.37 years. The mean BMI of the participants was 24.94±4.03 kg/m2, and the mean BMI of males was significantly higher compared to females (p